E-KYC Ticketing System (International Journal of Engineering and Computer Science, 2017)
The e-KYC ticketing system is the new way to book the tickets like bus ticket, train ticket, flight ticket, and other ticket bookings. The main purpose of the e-KYC ticketing system is to ensure the safe and secure journey of oneself and other fellow passengers. The e-KYC ticketing System is a new way to verify the passengers having journey on bus, train, flight etc. The e-KYC system permits ticket booking to the verified passengers only. This system will ask the Universe Identity Number as we have universe identity in India like Aadhar Card. Without the Aadhar card people will not be able to travel by any mode of transport. The e-KYC ticketing system uses two way verifications. The first verification happened before booking the ticket. The user needs to give his Aadhar card number to register them on the website. If they are not having Aadhar card then they cannot book the ticket. The second verification takes place when the TT comes to check the ticket. Her e TT will be having a device which will ask the ticket number and the thumb impression of the passenger. This thumb print will be matched with the existing database. If it match then he can travel in the train else an e-mail will be sent to railway department and the journey of the particular pass anger will be denied.